Modern Pollen Assemblages in Typical Agro-Pastoral Ecotone in the Eastern Tibetan Plateau and Its Implications for Anthropogenic Activities - Duan, Ronglei; Wei, Haicheng; Hou, Guangliang; Gao, Jingyi; Du, Yongsheng; Qin, Zhanjie (Frontiers in Ecology and Evolution, 2021)
Long-term evolution of human-environment interaction in the Qinghai-Tibetan Plateau (QTP) has been discussed intensively in recent years. The identification of human-related pollen types may help explore the coupled process of climate change, ecological response and anthropogenic activities on the QTP. The aim of this study is to evaluate the impact of anthropogenic activities on surface pollen assemblages and identify pollen indicators associated with grazing and cultivation in typical agro-pastoral ecotone of the eastern QTP. Totally 84 surface samples were analyzed from ﬁve vegetational communities in the eastern QTP, which are identiﬁable based on surface pollen assemblages. Principal component analysis of 29 pollen types and two supplementary variables of human inﬂuences were used to assess the impact of anthropogenic activities on surface pollen assemblages in eastern QTP. Severe grazing led to increase of Rosaceae, Ranunculaceae, Fabaceae, Taraxacum-Type, Aster-type and Saussurea-Type in pollen assemblages. Highland agricultural cultivation can be identified by the content and morphological characteristic of Brassiaceae and Cerealia Poaceae pollen. The aerial dispersed distances of Brassiaceae and Cerealia Poaceae pollen are very short, and domesticated herbivores are important factors, which disperse the Cerealia Poaceae pollen into pastures in agro-pastoral ecotone of the QTP. Modern pollen indicators of cultivation and grazing activity will provide precise references for fossil pollen study of prehistoric human activities in the QTP.